Polyelectrolyte nanocapsule probe for the determination of imidacloprid in agricultural food samples - Xiangdong Yu; Yansong Li; Xiaolei Liu; Bin Qiao; Yuying Yang; Yuanyuan Zhang; Pan Hu; Shiying Lu; Honglin Ren; Zengshan Liu; Mingyuan Liu; Yu Zhou (Food and Agricultural Immunology, 2019)
Layer-by-layer (LBL) technique is a well-established method for the formation of nanocapsules, which could encapsulate nanoparticles by polyelectrolyte and has received great interest in some areas of research. In this study, colloidal gold nanoparticles (AuNPs) were used as a vehicle for loading horseradish peroxidase (HRP), and AuNPs-HRP was encapsulated by using LBL technique to form a signal amplification nanocapsule probe. Based on the probe, an immunoassay was developed for the detection of imidacloprid in agricultural food samples (rice, pear and cabbage). The IC50 value of the assay was 0.11 ng mL−1 which was 8-9954 times lower than those of traditional ELISAs and well below the maximum residue limits (MRLs) permitted by the European Union (EU). The recoveries of imidacloprid from three different samples were 80.34–120.84% that had a good correlation (R2 = 0.9739) with those obtained by the commercial kit. The developed assay could provide a sensitive method for detection of imidacloprid.